Dinamika Hubungan Muslim-Kristen di Surakarta, 1999-2000 - Adif Fahrizal (Universitas Gadjah Mada, 2014)
This article describes the dynamics of Muslim-Christian relations in Surakarta during democratic transition era after New Order demise. This article uses history method consists of heuristic, critics, interpretation, and historiography. Based on the research it is known that the dynamics of Muslim-Christian relations during initial years of Reform era (1999-2000) was shaped by solidarity actions for communal conflict in Maluku and “blasphemy” case that ended in the court. In both cases the role of groups that carried religious identities have prominent role. Such groups emerged after the fall of New Order which repressed all kind of expressions and groups that was considered disrupt harmony by using primordial sentiments, including religious sentiment.